Rethinking international and domestic financing for HIV in low and middle income countries - Manning, R; Sterck, O (Wiley, 2017)
The scaling up of treatment for HIV across the world has been one of the most significant recent achievements in international health. But the commitment on antiretroviral treatment also creates a financial liability which is large and insufficiently recognized. In this paper, we explore how this financial liability could be met by domestic and international sources. We argue that (1) governments and donors should recognize the magnitude of the problem and develop tools to manage the liability; (2) allocation of aid should be more rational, transparent and sustainable; (3) more fiscal space should be created domestically; (4) borrowing offers some limited potential for prevention interventions characterized by high returns on investment and (5) efficiency gains, while not in themselves likely to bridge the resourcing gap, should be energetically pursued.